Análise de gêneros em contextos específicos: organização retórica e construção de sentidos no resumo de comunicação para eventos acadêmicos. - Oliveira, John Helio Porangaba de (2017)
The question of genre analysis in specific contexts has represented a study approach that explicitly and in depth knowledge about the construction, interpretation and use of genres in the most diverse situations, in the use of language. Our objective was to analyze the genre communication abstract from the point of view of the construction of meaning, observing text and context, context of production and rhetorical organization of the genre. The analysis was carried out with 60 communication abstracts taken from abstracts of three academic events, occurred in the year 2015. Among others, our theoretical bases have undergone the understanding of genre colony (BHATIA, [1998] 2009, 2004, BEZERRA 2006, 2007), genre chain (NOBRE, BIASI-RODRIGUES, 2012) and context theory (VAN DIJK, 2012). For the trajectory of analysis of this genre, we start from rhetorical organization studies of broad comprehension, from which we elaborate a standard model, suitable for analysis of the specific communication abstract. The trajectory also went through the understanding of genres as a communicative event, a dynamic entity that suits the context and interactive situations of the text participants (SWALES, [1990] 2008). In our discussions and results, we conclude that the respective genre is a result of academic and professional practices interpreted by producers, recipients and users on the terms genre and context. We conclude that the genre communication abstract is marked by linguistic and rhetorical actions, whose marks indicate the informative focus of the sentence and the rhetorical strategy that composes rhetorical movements, which in turn perform the genre. This genre builds meaning in the relation between genre and context as linguistic and rhetorical communicative actions in the dynamics of language with your norms, values and interpretations for a specific production.